Joint effects of individual socioeconomic status and residential neighborhood context on vaginal microbiome composition - Dixon, Meredith; Dunlop, Anne L.; Corwin, Elizabeth J.; Kramer, Michael R. (Frontiers in Public Health, 2023)
The vaginal microbiome is a dynamic ecosystem that is important for women’s health. Its composition has been associated with risk for menopausal symptoms, sexually transmitted infections, gynecologic cancer, and preterm birth. Conventional risk factors for a vaginal microbiome linked with these adverse health outcomes include sexual behaviors, hygiene practices, individual social factors, and stress levels. However, there has been limited research on socio-contextual determinants, and whether neighborhood context modifies the association with individual socioeconomic factors. Socioeconomically diverse pregnant African American women in Atlanta, Georgia (n=439) provided residential addresses and first trimester vaginal swab samples, which underwent sequencing, taxonomic classification, and assignment into mutually exclusive CST (community state types) via hierarchical clustering. Linear probability models were used to estimate prevalence differences (PD) for the associations of neighborhood factors with vaginal microbiome CST and to evaluate for additive interaction with maternal level of education, health insurance type, and recruitment hospital. Factors such as higher (vs. lower) maternal education, private (vs. public) insurance, and private (vs. public) hospital were associated with higher prevalence of Lactobacillus-dominant vaginal microbiome CSTs typically associated with better health outcomes. When considering the joint effects of these individual socioeconomic status and residential neighborhood factors on vaginal microbiome CST, most combinations showed a greater than additive effect among the doubly exposed; however, in the case of local income homogeneity and local racial homogeneity, there was evidence of a crossover effect between those with less-advantaged individual socioeconomic status and those with more-advantaged individual socioeconomic status. Compared to women at the public hospital who lived in economically diverse neighborhoods, women at the private hospital who lived in economically diverse neighborhoods had a 21.9% higher prevalence of Lactobacillus-dominant CSTs, while women at the private hospital who lived in less economically diverse neighborhoods (the doubly exposed) had only an 11.7% higher prevalence of Lactobacillus-dominant CSTs, showing a crossover effect (interaction term p-value = 0.004). In this study, aspects of residential neighborhood context were experienced differently by women on the basis of their individual resources, and the joint effects of these exposures on vaginal microbiome CST showed a departure from simple additivity for some factors.